Problem Hakim Mediasi dalam Melaksanakan Mediasi terhadap Kasus Perceraian pada Masa Pandemi Covid-19 di Pengadilan Agama Kelas 1B Kayuagung - Qodariah Barkah; Abi Tandore (Wajah Hukum, 2022)
The implementation of divorce mediation at the Kayuagung Class IB Religious Court during the pandemic has not been successful, so the author aims to find the problems of the mediator judge in conducting the mediation. This research uses the type of field research. Field data were obtained through direct interviews with mediator judges at Pengadilan Agama Kelas 1B Kayuagung. The approach method uses an empirical juridical approach. The results of this study found that there are two things that become the problem of the mediator, namely technical and non-technical aspects. The technical aspect is related to the limitations of experts and time, while the non-technical aspect lies in the determination, absence of the parties, less active participation in the mediation process, lack of openness in conveying problems and the ego nature of each party. Thus, what can be done is to add a special certified mediator and not from a judge; seek training and coaching related to marriage as well as mediator skills in conducting mediation.